Development of an Index for Measuring Islamic Bank CSR Disclosures in Indonesia - Dewi, Liana (el-Jizya : Jurnal Ekonomi Islam, 2024)
Measuring the disclosure of social activities carried out by Islamic banks is very important. However, the results of measuring the disclosure of social activities of Islamic banks in Indonesia still need to be higher when measured by the current CSR disclosure measurement index. The CSR disclosure measurement index often used in related research comes from research results in various countries in the Middle East and Southeast Asia. This is one of the considerations that causes the level of CSR disclosure of Islamic banks in Indonesia to be relatively low. Studies on developing an index for measuring CSR disclosure of Islamic banks in Indonesia are based on Sharia enterprise theory (SET). Based on the results of literacy studies of related research conducted in the Middle East, Southeast Asia, and Indonesia, several assessment dimension criteria need to be developed, including those related to the obligation of Islamic banks to report their social activities from the start of their establishment, environmental awareness education for employees, use of environmentally friendly materials. to support operational activities and collaboration with social communities in order to achieve acceleration and equal distribution of community welfare.